GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 17389 species occurrences available in GBIF matching the query: TaxonKey: Characiformes Geometry: POLYGON((-59.414062 -12.897489,-53.789062 -8.407168,-38.671874 -9.795677,-34.453125 -14.604847,-31.992187 -29.228890,-50.625 -37.996162,-63.28125 -39.909736,-69.257812 -25.799891,-71.71875 -15.961329,-59.414062 -12.897489)) HasCoordinate: true HasGeospatialIssue: false. The dataset includes 17389 records from 41 constituent datasets: 315 records from International Barcode of Life project (iBOL). 768 records from Fishbase. 9 records from Occurrence records of southern African aquatic biodiversity. 5 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 141 records from The Fish Collection at the Zoologische Staatssammlung München. 13 records from CUMV Fish Collection (Arctos). 1 records from MVZ Hildebrand Collection (Arctos). 820 records from Museum of Comparative Zoology, Harvard University. 359 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 146 records from Ichthyology Collection - Royal Ontario Museum. 7 records from iNaturalist Research-grade Observations. 350 records from Bolivian Amazon lowland fish metacommunity data. 488 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 930 records from CAS Ichthyology (ICH). 1133 records from NMNH occurrence DwC-A. 19 records from Diveboard - Scuba diving citizen science observations. 1 records from Colección Ictiológica del CENPAT-CONICET. 12 records from SysTax - Zoological Collections. 11 records from Natural History Museum (London) Collection Specimens. 6 records from Harold W. Manter Laboratory of Parasitology Collection. 680 records from Collection Ichthyologie - SNSD. 3 records from Paleobiology Database. 1 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 1 records from UCM Fish Collection (Arctos). 13 records from KUBI Ichthyology Collection. 7 records from Oligosarcus perdido (Characiformes, Characidae), a new species of freshwater fish from Serra da Bodoquena, upper Rio Paraguai basin, Brazil.. 5 records from Global subterranean fishes. 24 records from Collection Pisces SMF. 928 records from Geographically tagged INSDC sequences. 151 records from Field Museum of Natural History (Zoology) Fish Collection. 2 records from Oregon State Ichthyology Collection. 225 records from Coleção de Ictiologia do Museu de Ciências Naturais do Centro Universitário Univates (ZIUMCN-UNIVATES). 5080 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 2 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 14 records from A new species of the freshwater fish genus Astyanax (Ostariophysi: Characidae) from the rio Iguacu basin, southeastern Brazil.. 543 records from Ictiologia Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 63 records from AUM Fish Collection. 3429 records from Occurrences in SinBIOTA. 9 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 554 records from UF FLMNH Ichthyology. 121 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences